Wheat dwarf virus vectors replicate and express foreign genes in cells of monocotyledonous plants. - Matzeit, V (1991)
Wheat dwarf virus (WDV) is a geminivirus that infects monocotyledonous plants. To exploit the potential of WDV as a replicative gene vector, we developed a transient replication and expression system based on the transfection of protoplasts derived from Triticum monococcum suspension culture cells. Cloned genomic copies of various WDV isolates as well as mutants constructed in vitro were introduced into the protoplasts and assayed for their ability to replicate. As a result, regions of the WDV genome necessary or dispensable for the viral DNA replication could be defined. In addition, the gene encoding the viral capsid protein was replaced by three different bacterial marker genes, neomycin phosphotransferase, chloramphenicol acetyltransferase, and beta-galactosidase. The beta-galactosidase gene doubled the size of the WDV genome. The replication of the recombinant WDV genomes and the expression of these genes were monitored in suspension culture cells of T. monococcum. The potential of replicative expression vectors based on the WDV genome is discussed.